Penerimaan Pendapatan Daerah Sektor Pajak Bapenda Kabupaten Karawang - Satrio Budi Prakoso; Ujang Suherman (Manajemen Kreatif Jurnal, 2024)
This article aims to find out about the process of receiving revenue from the Karawang BAPENDA tax sector, with a focus on recording, reporting. the reason can provide valuable insight for local governments in increasing effectiveness and efficiency in local tax management. this research method is qualitative using descriptive analysis, which is a research method that tries to describe the object. The results of the study indicate the process of receiving local revenue from the Karawang BAPENDA tax sector by using Sipadi and after being inputted, a tax form is made, namely SSPD, to be submitted to employees and then paid according to tax and will receive STBP and STS will also be made by using the system, it will be more efficient in errors between systems and humans. obstacles in the receipt of local revenue by Bapenda Karawang related to deposit certificates, local tax payment certificates, and proof of payment certificates include data entry errors, incomplete documents, difficulty verifying payments, and technical problems in administration and reporting systems. To address these issues, Bapenda Karawang could improve officer training, use advanced information technology, and increase transparency of financial reporting. Additional measures include strengthening coordination between units, periodic evaluation of systems and procedures, and providing easy and clear access to local revenue information to the public.